The hippocampus and exercise: histological correlates of MR-detected volume changes - Biedermann, Sarah Violetta; Ende, Gabriele; Gass, Peter (Brain structure & function, 2016)
Growing evidence indicates that physical exercise increases hippocampal volume. This has consistently been shown in mice and men using magnetic resonance imaging. On the other hand, histological studies have reported profound alterations on a cellular level including increased adult hippocampal neurogenesis after exercise. A combined investigation of both phenomena has not been documented so far although a causal role of adult neurogenesis for increased hippocampal volume has been suggested before. We investigated 20 voluntary wheel running and 20 sedentary mice after a period of 2 month voluntary wheel running. Half of each group received focalized hippocampal irradiation to inhibit neurogenesis prior to wheel running. Structural MRI and histological investigations concerning newborn neurons (DCX), glial cells (GFAP), microglia, proliferating and pyknotic cells, neuronal activation, as well as blood vessel density and arborisation were performed. In a regression model, neurogenesis was the marker best explaining hippocampal gray matter volume. Individual analyses showed a positive correlation of gray matter volume with DCX-positive newborn neurons in the subgroups, too. GFAP-positive cells significantly interacted with gray matter volume with a positive correlation in sham-irradiated mice and no correlation in irradiated mice. Although neurogenesis appears to be an important marker of higher hippocampal gray matter volume, a monocausal relationship was not indicated, requesting further investigations.
Gesehen am 02.04.2019
Published online: 31 December 2014